MCM8-9 helicase activity protects primordial germ cell development to prevent premature ovarian insufficiency - Xiaofei Jiao; Zhifang Li; Zhenghui Tang; Jun Xu; Lin-Yu Lu; Yidan Liu (Proceedings of the National Academy of Sciences, 2026)
MCM8 and MCM9 form a hexameric helicase critical for homologous recombination (HR). While their variants are strongly associated with premature ovarian insufficiency (POI), with many clustering within their AAA+ ATPase domains, the requirement for their helicase activity remains unknown. Here, we show that MCM8-9’s helicase activity is essential for ovarian reserve preservation and POI prevention. Using a series of helicase-deficient mouse models, we demonstrate that this activity is dispensable for meiotic recombination but critically required for mitotic HR and primordial germ cell (PGC) development. The two distinct ATPase active sites of MCM8-9 exhibit marked functional asymmetry, a property regulated by residues within their Walker B motifs. Despite this asymmetry, both ATPase active sites are equally essential for MCM8-9’s function in HR, PGC development, ovarian reserve preservation, and POI prevention. Our findings establish a direct mechanistic link between compromised MCM8-9 helicase activity and POI pathogenesis through its essential role in PGC development.